Levels of Land Cover Density on Carbon Reserves and Income in Dongo Baru Community Forest (HKm) - Jayadi, Andi; Idris, Muhammad Husni; Markum, Markum (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Community Forest (HKm) in Dongo Baru, Mount Rinjani forest area, in land management applies a mixed agroforestry pattern. The application of this pattern is the result of forest rehabilitation activities covering 138 ha in 2019. This HKm has a variety of different types of land management in one management area. This study aims to describe the condition of HKm using an environmental approach by estimating carbon stock data and economic value by looking at the value of arrive efficiency. The strategy utilized in this inquire about is graphic method by means of observation, Center Gather Discourse, and interviews, to 27 respondents / owners of land economic aspects by taking carbon stock data to 27 farmer-owned land. The environmental assessment to measure carbon stocks used a sample of 27 plots, measuring 50m x 20m for trees, 10m x 10m for poles, and 5m x 5m for saplings. The plots represent the density level of the forest area, i.e. dense, medium, not dense. Determination of forest density classification using Landsat-7 satellite image analysis in 2022. Based on the comes about within the ponder, it can be concluded that there are 3 density classifications that exist in the Dongo Baru HKm forest area, namely Meeting density, Moderately Meeting density and Not Meeting density. their respective incomes are meeting land density (Rp. 21,273,889), Moderately Meeting land density (Rp. 19,210,333) and Not Meeting land density (Rp. 22,431,556). Meeting land has carbon stock (256.86 tonnes/ha), Moderately Meeting land has carbon stock (95.34), and Not Meeting land has carbon stock (52.90 tonnes/ha). Land management with the density of Rapat land is considered to have fulfilled the principles of forest management from the economic and environmental aspects.